1983
DOI: 10.1164/arrd.1983.128.3.501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Obesity on Respiratory Function

Abstract: Obesity, because it alters the relationship between the lungs, chest wall, and diaphragm, has been expected to alter respiratory function. We studied 43 massively obese but otherwise normal, nonsmoking, young adults with spirometry, lung volume measurement by nitrogen washout, and single-breath diffusing capacity for carbon monoxide (DLCO). Changes in respiratory function were of two types, those that changed in proportion to degree of obesity--expiratory reserve volume (ERV) and DLCO--and those that changed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
298
6
23

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(352 citation statements)
references
References 23 publications
25
298
6
23
Order By: Relevance
“…[26][27][28] A consistent negative association between WC and pulmonary function has recently been demonstrated in normal weight, overweight and obese subjects, suggesting that FM stored in the abdominal cavity, particularly visceral fat, most likely directly impedes the descent of the diaphragm leading to primarily restrictive respiration impairment. 28 Among obese subjects, there is evidence of peripheral airway obstruction, as manifested by air trapping and reduced maximum expiratory flow rates.…”
Section: Discussionmentioning
confidence: 71%
“…[26][27][28] A consistent negative association between WC and pulmonary function has recently been demonstrated in normal weight, overweight and obese subjects, suggesting that FM stored in the abdominal cavity, particularly visceral fat, most likely directly impedes the descent of the diaphragm leading to primarily restrictive respiration impairment. 28 Among obese subjects, there is evidence of peripheral airway obstruction, as manifested by air trapping and reduced maximum expiratory flow rates.…”
Section: Discussionmentioning
confidence: 71%
“…This reduction does not represent an actual pulmonary restriction, but rather a restrictive behavior which usually tends to improve after weight loss as shown by the mean postoperative value of 3.07 l compared to the preoperative value of value of 2.60 l. Other studies have also reported a similar improvement of FRC over a six month period after the Fobi-Capella operation 6,9,10 .…”
Section: Correlation Between Percent Loss Of Weight Excess and Pulmonmentioning
confidence: 83%
“…Many literature reports emphasize the fact that morbidly obese patients have reduced expiratory reserve volume (ERV) and reduced al functional residual capacity (FRC), as well as restrictive respiratory behavior in many cases 10,11 . In severely obese patients, ventilatory normality is reestablished after weight loss as a consequence of increased FRC, residual volume (RV), total lung capacity (TLC), and ERV.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, increases in total body mass are associated with a decline in ERV, and therefore FRC; consistent with the notion that this effect seems to be evident only in severely obese subjects, we were not able to find a negative effect of weight on the LV of males (Table 5). On the other hand, in females, weight was positively related to IC and negatively to RV/TLC (Table 5): the first effect could represent the known positive relation between body mass and PImax (since the inspiratory capacity is closely related to respiratory muscle strength) and the latter effect, a reduction in ERV due to a more central deposition of fat in females (39).…”
Section: Discussionmentioning
confidence: 99%